REDESIGN USER INTERFACE WEBSITE UNIVERSITAS BINA SARANA INFORMATIKA MENGGUNAKAN METODE DESIGN THINKING DAN SYSTEM USABILITY SCALE (SUS) - Novianti, Diah (Universitas Lampung, 2024)
The use of information technology and the internet has become an indispensable necessity, especially in the education sector. Bina Sarana Informatika University (BSI) faces the challenge of maintaining competitiveness through an informative, user-friendly, and responsive official website. This research employs the System Usability Scale (SUS) method and a design thinking approach to enhance the usability of the BSI website. The research results demonstrate a significant increase in user satisfaction and experience after the redesign process of BSI website's UI/UX, with the SUS score improving from 49 to 92. This underscores the importance of considering user needs in information technology development, particularly in higher education contexts. In conclusion, the design thinking approach and usability evaluation using the SUS method are effective strategies in improving the usability quality of educational websites and supporting a better user experience.